Faktor yang Mempengaruhi Keputusan Wakaf : Systematic Literature Review - Ari Setiawan; Wahyudin Wahyudin (ITB AAS INDONESIA Surakarta, 2023)
This study examines the key factors that determine waqf decisions. The author performed a thorough examination of 21 publications released between 2019 and 2023, which were indexed by Scopus and sinta.kemdikbud.go.id. The objective of this analysis is to discern the factors that influence waqf decisions in the current body of literature. Prior to completing an extensive examination of the literature review to provide evidence for future research, data is gathered, examined, and assessed. Research findings indicate that multiple elements have been found to exert influence on waqf decisions. The factors encompassed in this list are age, education level, religiosity, attitudes, subjective norms, knowledge, understanding, income, performance expectations, business expectations, crowdfunding platform facilities, social incentives, experience, trust in waqf organisations, and waqif views. The decision was not influenced by the following factors: knowledge, employment, education, information medium, distance to the location of the waqf institution, faith in the waqf institution, fundraising approach, and social influence. Subsequent research endeavours should focus on investigating the determinants that impact waqf in order to enhance the level of waqf acceptability. This study has the potential to have substantial social ramifications for multiple parties engaged in waqf, including waqf institutions, waqifs, and waqf recipients.